Customer Perception and Literacy regarding the Implementation Of Green Banking at Bank BCA, Tbk (Gen-Z Case Study) - Fiska , Anggraini; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
Awareness of environmental issues and climate change has increased, the concept of "green banking" or sustainable banking has become increasingly important to overcome the climate crisis. Not only related to banking products, but also shows awareness of the potential for ecological disasters that could hamper the country’s economic growth. In this context, customer perception and literacy have an influence in supporting the improvement and development of green banking programs. Thus, the aim of this research is to find out, analyze and explain how customer perception and literacy influence the implementation of Green Banking. This research adopts a quantitative descriptive approach method. Sampling in this study was carried out using a non-probability sampling method using purposive sampling techniques. Data for research was obtained through the distribution of questionnaires distributed via Google Forms to 100 respondents who were BCA Bank customers in Karawang. The selection of the number of respondents was based on the Lemeshow formula with an unknown population size. The data analysis method applied is Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach, carried out with the help of SmartPLS 3.2.9 software. The results of the analysis show that there is a partial positive and significant influence of the Customer Perception and Literacy variables on the implementation of Green Banking.